A graded phononic crystal with decoupled double defects for broadband energy localization. (1st October 2020) - Jo, Soo-Ho; Yoon, Heonjun; Shin, Yong Chang; Youn, Byeng D.
Highlights: A graded phononic crystal (PnC) with decoupled double defects is newly proposed. The graded PnC is a superposition of two graded PnCs with a single defect. The graded PnC enables to separately design defect band frequencies of each defect. The graded PnC can achieve broadband energy localization. Abstract: Several research efforts have been devoted to exploring defect modes of uniform phononic crystals (PnCs) with single or double defects. However, they have difficulties in achieving broadband energy localization under realistic environments. This study thus proposes a new design concept of a graded PnC with double defects for broadband energy localization. A graded PnC refers to a PnC built by varying one or more design variables of its lattices. The double defects are introduced to be sufficiently far from each other to make them decoupled; each of the defects behaves as an independent single defect. Unlike a uniform PnC, the graded PnC enables to separately design defect band frequencies corresponding to each of the double defects by changing a degree of the variation in the height of the circular stub. The graded PnC with double defects can broaden the bandwidth for elastic wave localization. Graphical abstract: Image, graphical abstract